8. The Evolution of Engraving in Moldova - Savițkaia-Baraghin Iarîna (Sciendo, 2022)
This paper achieves some landmarks regarding the appearance and evolution of engraving in Moldova within the medieval, modern and contemporary art periods and aims to highlight the evolution of engraving and achievements in the art of engraving in the historical territory of Moldova, but also to establish the basic stages of the evolution of engraving and regional interferences in relation to European engraving. If we follow the comparative evolution of the genus in various neighboring regions, we find that each area has its own specificity and particularities. The approach to this issue is related to the general aspects that conditioned the development of religious engraving, but also to the local tradition, which has evolved in close connection with the respective process in European countries.